Numerical investigation of three-dimensional hybrid Cu–Al2O3/water nanofluid flow over a stretching sheet with effecting Lorentz force subject to Newtonian heating - Devi, S. Suriya Uma; Devi, S.P. Anjali (Canadian journal of physics, 2016)
This work compares the heat transfer characteristics of traditional nanofluid with that of emerging hybrid nanofluid. Hybrid nanofluid, a new type of conventional fluid, has been used toward the enhancement of heat transfer in the boundary layer flow. A new model of thermophysical properties is employed to investigate the effects of Lorentz force over a three-dimensional stretching surface subject to Newtonian heating. Comparisons are obtained through the numerical parametric study, which has been carried out to explore the effects of various physical parameters involved in the problem. From this study it is observed that the heat transfer rate of hybrid nanofluid (Cu–Al 2 O 3 /water) is higher than nanofluid (Cu/water) even in the presence of a magnetic field environment. By opting to use different and appropriate nanoparticle proportions in hybrid nanofluid, the desired heat transfer rate can be achieved.